The biostratigraphy of the offshore Niger delta during the Late Quaternary: Complexities and progress of dating techniques - Onema Adojoh; Fabienne Marret-Davies; Robert Duller; Peter Osterloff; Francisca Oboh-Ikuenobe; Malcolm Hart; Christopher Smart (Quaternary Science Advances, 2020)
The Late Quaternary marine sediments from the Niger Delta lacks an age model using conventional radiocarbon dating due to the rarity of calcareous macrofossils. The proprietary nature of material drilled by companies prospecting for hydrocarbons in the Niger Delta basin, and in the rare cases when samples are available for study as well as freshwater dilution from continental runoff have contributed to this dearth of knowledge. The availability of three shallow marine (∼3 m) gravity cores obtained from the eastern, central, and western parts of the Niger Delta provides the opportunity for biostratigraphy utilising well-preserved marker species of planktonic foraminifera and calcareous nannofossils in the sediments. The last occurrence (LO) of planktonic foraminiferal species Globorotalia truncatulinoides (late Pleistocene) (MIS 2) and the first occurrence (FO) of Globorotalia tumida (Holocene) (MIS 1) are used to identify two interval zones in the gravity cores. The presence of the calcareous nannofossil Gephyrocapsa oceanica (all <3 μm in size) supports a late Pleistocene age (NN19 Zone) for the lower interval. In addition, an increase in the abundance of Emiliania huxleyi up-section is an indication of early Holocene age (NN20-NN21) for the upper interval.